Validation of the American Association for the Surgery of Trauma Emergency General Surgery Grading System for Colorectal Resection: An EAST Multicenter Study. Issue 5 (May 2022) - Aicher, Brittany O.; Betancourt-Ramirez, Alejandro; Grossman, Michael D.; Heise, Holly; Schroeppel, Thomas J.; Hernandez, Matthew C.; Zielinski, Martin D.; Kongkaewpaisan, Napaporn; Kaafarani, Haytham M. A.; Wagner, Afton; Grabo, Daniel; Scott, Michael; et al.
Background: The American Association for the Surgery of Trauma (AAST) has developed a grading system for emergency general surgery (EGS) conditions. We sought to validate the AAST EGS grades for patients undergoing urgent/emergent colorectal resection. Methods: Patients enrolled in the "Eastern Association for the Surgery of Trauma Multicenter Colorectal Resection in EGS—to anastomose or not to anastomose" study undergoing urgent/emergent surgery for obstruction, ischemia, or diverticulitis were included. Baseline demographics, comorbidity severity as defined by Charlson comorbidity index (CCI), procedure type, and AAST grade were prospectively collected. Outcomes included length of stay (LOS) in-hospital mortality, and surgical complications (superficial/deep/organ-space surgical site infection, anastomotic leak, stoma complication, fascial dehiscence, and need for further intervention). Multivariable logistic regression models were used to describe outcomes and risk factors for surgical complication or mortality. Results: There were 367 patients, with a mean (± SD) age of 62 ± 15 years. 39% were women. The median interquartile range (IQR) CCI was 4 (2-6). Overall, the pathologies encompassed the following AAST EGS grades: I (17, 5%), II (54, 15%), III (115, 31%), IV (95, 26%), and V (86, 23%). Management included laparoscopic (24, 7%), open (319, 87%), and laparoscopy converted to laparotomy (24, 6%). Higher AAST grade was associated with laparotomy ( P = .01). The median LOS was 13 days (8-22). At least 1 surgical complication occurred in 33% of patients and the mortality rate was 14%. Development of at least 1 surgical complication, need for unplanned intervention, mortality, and increased LOS were associated with increasing AAST severity grade. On multivariable analysis, factors predictive of in-hospital mortality included AAST organ grade, CCI, and preoperative vasopressor use (odds ratio (OR) 1.9, 1.6, 3.1, respectively). The American Association for the Surgery of Trauma emergency general surgery grade was also associated with the development of at least 1 surgical complication (OR 2.5), while CCI, preoperative vasopressor use, respiratory failure, and pneumoperitoneum were not. Conclusion: The American Association for the Surgery of Trauma emergency general surgery grading systems display construct validity for mortality and surgical complications after urgent/emergent colorectal resection. These results support incorporation of AAST EGS grades for quality benchmarking and surgical outcomes research.